The Brandmindset™ - Knapp, Duane E. (McGraw-Hill, 2000)
Aimed at managers, not just marketers, a famed consultant presents a powerful prescription for understanding, building, and sustaining brand equity--based on the experiences of Starbucks, Citicorp, Whirlpool, Lexus, Hallmark, and other internationally renowned brands.